The relationship between the immune system activity and the bacterial vaginosis development - Hruzevskyi, O. A.; Minukhin, V. V.; Vastyanov, R. S. (Journal of Education, Health and Sport, 2020)
The main cause of bacterial vaginosis (BV) is immunodeficiency which is both systemic and local in nature and increases in parallel to a dysbiosis grade deepening. It is of great importance to link the indicators of BV-associated microbiota with individual indicators of systemic immune responses. The aim of the study is to establish a relationship between the immune system state and the development of various grades bacterial dysbiosis and BV. The study selected 298 women, who were divided into groups according to the index of conditionally pathogenic microflora (ICPM): in normocenosis ICPM was lower than -3 lg GE/sample (n = 53); in grade I dysbiosis it was from -3 to -1 lg GE/sample (n = 128); and in grade II dysbiosis (BV) it was more than -1 lg GE/sample (n = 117). Molecular-genetic studies of the scraping of epithelium from the posterolateral vaginal paries were performed using the method of polymerase chain reaction (DNA technology, RF). Optional and obligate anaerobes, myco- and ureplasms and yeast fungi were quantified. Content in the blood of fractions of T-and B-lymphocytes, immunoglobulins, cytokines, complement, lymphocyte phagocytic activity (LPA), 21 indicators in total) were determined using standard immunological methods. Interrelation between the microbial biocenosis with the considered indicators was studied using the regression analysis (Statistica 10; StatSoft, Inc.,USA). In normocenosis, normobiota indicator (NBI) was determined by activation of complement (C4), PA – as well by activation of complement (C3) and by content of sIgA in blood; ObA and YF – by γ-INF level, and YF – also by IL8, IL10 and sIgA levels; ICPM effective value was determined by the number of CD22+ lymphocytes. In grade I dysbiosis, NBI depended on the number of CD22+ lymphocytes, IL6, IgM, IgG, LPI, CIC, IL10, which indicated the implementation of various mechanisms and involvement of almost all of the immune system levers to compensate for dysbiosis at the beginning of its formation. In grade I dysbiosis, ObA amount was also affected by IL6 and IL10, and MU amount – by IL1β and IgG. In grade II dysbiosis, no factors affected NBI, which indicated that the dysbiotic processes went beyond the control of the immune system. Content of IL1β in blood reflected a shift of the ICPM: when its level exceeded 24.6 pg/ml, grade II dysbiosis was present; at IL1β level from 9.6 pg/ml to 24.6 pg/ml – it was grade I dysbiosis, and at IL1β level less than 9.6 pg/ml – it was normocenosis. Factors, which anaerobic dysbiosis was the trigger for, were activation of the humoral immunity (IgG secretion) and IL10 increase. General analysis of the interrelation between the immune system indicators with the number of pathogenic microbiota revealed the development of systemic combined immunodeficiency and “slipping” of the most pathogenic microorganisms out of the control of the immune system.